SINTESIS PERMUKAAN KACA HIDROFOBIK MELALUI KOMBINASI TiO2/ASAM STEARAT UNTUK APLIKASI MATERIAL SELF-CLEANING - Diana Vanda Wellia; Febby Alvionita; Syukri Arief (Journal of Research and Education Chemistry, 2020)
The surface of ultrahydrophobic glass has been successfully prepared using the combination of TiO2 and stearic acid. TiO2 was used to increase the surface roughness, while stearing acid was a surface modifier. The peroxo sol-gel method has been used to synthesize TiO2 precursors on the glass layer followed by modification of stearic acid. The maximal water contact angle of 141o has been obtained for the composition of 0.4 grams of stearic acid and 20 mL of ethanol (NKTS-2%). AFM analysis showed the roughness of NKTS-2% is 4,15 nm, which was greater than the pure glass. FTIR analysis also showed vibration of C=O (carbonyl) at 1697cm-1 indicating the chemical interaction between TiO2 and stearic acid. EDX spectrum analysis of TiO2/stearic acid (TiO2/C18H36O2) showed the existence of titanium, oxygen, and carbon. The optimum sample (NKTS-2%) showed a good transparency and self-cleaning properties compared to pure glass